Pengaruh Model Kooperatif Tipe TGT (Teams Games Tournament) Berbasis Quizizz Terhadap Hasil Belajar Pendidikan Pancasila Peserta Didik Kelas III SD Negeri 1 Metro Barat - Haya Asyifa; Ujang Efendi; Muhisom Muhisom; Frida Destini (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2025)
This research is motivated by the low learning outcomes of Pancasila Education of third-grade students of SD Negeri 1 Metro Barat. This research aims to analyze: (1) the influence of the Quizizz-based TGT cooperative learning model on the learning outcomes of Pancasila Education of third-grade students of SD Negeri 1 Metro Barat, and (2) the differences in learning outcomes between students who use the Quizizz-based TGT (Teams Games Tournament) learning model and students who learn using the NHT (Numbered Heads Together) learning model. This research uses a quasi-experimental design method with a pretest-posttest control group design. The research population is all third-grade students of SD Negeri 1 Metro Barat with a total of 41 students. Data collection techniques are carried out through pretest and posttest tests, while data analysis uses a t-test to measure the significance of differences in learning outcomes between groups. The results of the study show that: (1) there is a significant influence on the learning outcomes of Pancasila Education of students before and after the implementation of the Quizizz-based TGT model, with a significance value (2-tailed) of 0.000. (2) There is a significant difference in learning outcomes between students who learn using the Quizizz-based TGT (Teams Games Tournament) model and students who use the NHT (Numbered Heads Together) model, with a significance value (2-tailed) of 0.001.